State administration in emergense situation: problems of legal providing - Кузніченко, Сергій Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In article the legislation which regulates activity of state structures in emergency situations is analyzed. Offers on improvement of system of the government in the specified sphere are developed.